Fault-tolerant Shunt Active Power Filter Based on Component Redundancy and Its Control Strategy - XU Qunwei; WANG Yue; ZHAN Jinxiang; CHEN Guozhu (Kongzhi Yu Xinxi Jishu)
Shunt active power filter (SAPF) is based on the three-phase six-switch topology. In order to improve its flexibility whenapplied in industrial field, it proposed a three-phase four-switch fault-tolerant SAPF based on component redundancy. The structure and operation mode of the fault-tolerant circuit were analyzed in details. Considering about the voltage fluctuation and unbalance of DC side capacitor when one-phase fault occurred, voltage stabilization control and equalization control were designed. Due to the circuit of threephase six-switch four-wire would be converted into three-phase four-switch three-wire system, corresponding control strategy in the fault-tolerant status was studied to guarantee the output symmetry among three-phase. Experimental results of a 50 kVA prototype have validated the efficiency and feasibility of the proposed control strategy.